Organic spectroscopic structure determination - Taber, Douglass F. (Oxford University Press, 2007)
Organic Spectroscopic Structure Determination is a sophomore-level book with emphasis on structure problem solving. It consists of four sections that attempt to engage the imagination of the student. Taber has arranged the material in such a way that the students can work the problems and learn the procedures on their own, minimizing the time taken in lecture. The first section contains three chapters of instruction on the methods of organic spectroscopy. The second contains fifty problems with just data sets of spectroscopic data. The third section is comprised of fifty problems that show starting materials and reaction conditions, with spectroscopic data for the product. The final section includes tables of spectroscopic data